An analysis of the role of AfCFTA investment facilitation protocol and strategies in the promotion of sustainable development in SADC Developing Countries: a comparative study - Kandjii, Nongee (Department of Commercial Law, 2024)
The Southern African Development Community (SADC), like other African Regional Economic Communities (RECs), was created in an effort to build beyond the economic, social, political and environmental fragmentation and damage brought about by colonial powers and the remnants of their control during the earliest post-colonial eras. With these integration efforts came the new-found need to address common regional problems such as abject poverty, unemployment, diseases and epidemics, as well as seemingly perpetual depletion of natural resources, amongst others, through adequate and globally-recognised developmental mechanisms such as sustainable development. This practise of observing development through the lens of sustainability became popular in the 1970s and 1980s, when researchers and economists noted the nexus between environmental well-being and the rate of economic progress. This was first recognised during the Stockholm Conference on Human Environment in 1972 and was later demonstrated in the Brundtland Report's findings in 1987. This dissertation reflects on the new African Continental Free Trade Agreement (AfCFTA) establishing the African Continental Free Trade Area, and its potential to promote sustainable development in the SADC through its Investment Protocol, and particularly through investment facilitation processes and strategies, in order to ultimately present a positive impact for socioeconomic and environmental development within the region. In its earliest chapters, the research unpacks the layered meanings of investment and sustainable development, as highlighted by the Salini case and scholarship of Melber and Southall, respectively, to create the context within which the discussion of SADC sustainability can occur through the AfCFTA. Furthermore, this nexus between investment and sustainable development is explored within the narrower lens of the AFCFTA and its specific Protocol on Investment and its position on sustainable development. The latter reveals that sustainable development lacks sufficient emphasis within the AfCFTA and this exposes both the crux of the problem statement of this minor dissertation, as well as the flaw of several modern Investment tools and protocols within the African investment framework. Lastly, this dissertation's brief view of the history of the SADC's perceptions and instruments for sustainable development in the region allows for a greater understanding of the foundations upon which the current AfCFTA is to advance sustainable development in the region. Moreover, this also presents the opportunity for a comparative exercise against international RECs such as the European Union and the recent economic structure formed by the United States-Mexico-Canada Agreement. These two are intentionally compared to the AfCFTA because of their direct references to the nexus between investment, the environment and sustainable development. Through this comparative analysis, the research displays not only the various strengths and shortcomings of the AfCFTA, but more importantly, the ways in which International Investment Agreements (IIAs) and instruments can be practically structured in order to promote sustainable development within a REC.